2020
DOI: 10.3390/su12125014
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Stocks during the Corona-Crash? News Attention vs. Rational Expectation

Abstract: We explore if the corona-crash 2020 was driven by news attention or rational expectations about the pandemic’s economic impact. Using a sample of 64 national stock markets covering 94% of the world’s GDP, we find the stock markets’ decline to be mainly associated with higher news attention and less with rational expectation. We estimate the economic cost from the news hype to amount to USD 3.5 trillion for the US and USD 200 billion on average for the rest of the G8 countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 42 publications
1
29
0
1
Order By: Relevance
“…In addition to contributing to the recent literature on the COVID-19 market reactions (e.g., [29][30][31][32][33]), our findings contribute to the ongoing debate over the performance of sustainable investments in the following ways. First, our study makes it possible to evaluate the financial performance of sustainable investments in times of exceptional crisis from a worldwide health emergency and by uncommon measures put in place by governments to preserve global health.…”
Section: Introductionmentioning
confidence: 55%
“…In addition to contributing to the recent literature on the COVID-19 market reactions (e.g., [29][30][31][32][33]), our findings contribute to the ongoing debate over the performance of sustainable investments in the following ways. First, our study makes it possible to evaluate the financial performance of sustainable investments in times of exceptional crisis from a worldwide health emergency and by uncommon measures put in place by governments to preserve global health.…”
Section: Introductionmentioning
confidence: 55%
“…It is thought that these figures reflect the pandemic very well and using the cumulative figures may be misleading. Moreover, a negative relationship between the pandemic indicators and the main indices is expected by considering recent studies (Adekoya and Kofi Nti 2020;Ahmed 2020;Al-Awadhi et al 2020;Ali, Alam, and Rizvi 2020;Ashraf 2020;Bahrini and Filfilan 2020;Baker et al 2020;Chowdhury and Abedin 2020;Corbet et al 2020;Engelhardt et al 2020;Erdem 2020;Gherghina, Armeanu, and Joldeș 2020;Kartal, Depren, and Kılıç Depren 2020;Liu et al 2020;Mazur, Dang, and Vega 2020;Narayan, Phan, and Liu 2020;Phan and Narayan 2020;Shehzad, Xiaoxing, and Kazouz 2020;Topcu and Gulal 2020;Zhang, Hu, and Ji 2020;Akhtaruzzaman, Boubaker, and Şensoy 2020a). However, there can be neutral nexus between the pandemic indicators and the main indices if the pandemic becomes very common and spreads to every country and it is perceived as a normal part of daily life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stock exchanges and stock market indices also react to pandemic diseases, such as Ebola and Severe Acute Respiratory Syndrome (SARS) outbreaks (Chen, Jang, and Kim 2007;Ichev and Marinč 2018). Naturally, stock exchange indices have been influenced deeply in these times (Engelhardt et al 2020). According to the volatility (VIX) index, the Covid-19 pandemic is the most significant global phenomenon that the world has ever faced (Bloomberg 2020).…”
mentioning
confidence: 99%
“…Regarding prior studies on investigating the economic impacts of COVID-19 outbreak, first, for the cross-country studies, Ashraf [ 24 ] finds the growth in the number of country-level confirmed cases of COVID-19 has a negative effect on stock markets based on the 64 countries over the period 22 January to 17 April 2020. In addition, Engelhardt et al [ 7 ] confirm that news attention of COVID-19 associate with the stock markets’ decline. Also, Zhang et al [ 4 ] show that the COVID-19 pandemic leads to an increase in global financial market risks based on the cross-country evidence.…”
Section: Background Literature and Hypothesis Developmentmentioning
confidence: 99%